Utilization of young and mature coconut water as substitute to coconut milk in Nata de Coco production. - Gerona, Ma. Jovie Gubatanga (1997.)
Nata de coco is one of the non-traditional coconut by-products. Small scale industries are using coconut milk as substrate in nata de coco production. Coconut milk can still be used in the preparation of other food stuffs. On the other hand, a large amount of coconut water is being discarded. The study aimed to: (1) determine the quality of nata produced from young coconut water, approximately 8-10 months old and from mature coconut water approximately 14 to 16 months old; and (2) compare the nata produced using the above-stated substrates with that produced from coconut milk. Two treatments with three replicates each were used. Nata production was carried for 10 days. The harvested nata slabs were processed into cubes which were then subjected to sensory evaluation. The following attributes were noted: evenness, thickness, texture and color. The thickness and weight of twenty randomly sampled nata cubes for each treatment were also determined by the use of Vernier caliper and Stanton top-loading balance. The control produced the cubes that have the greatest mean weight and thickness (4.584+-0.967g) and 0.667+-13 cm. respectively). However, the highest mean sensory evaluation rating for general acceptability was given to Treatment 2. One Way Analysis of Variance (ANOVA) of the weight and thickness of the cubes showed that there is a highly significant difference among the treatments. ANOVA of the sensory evaluation results showed that there is no significant difference between the texture, firmness and evenness of the nata cubes. However, a significant difference exists between the treatments for color and general acceptability. Based on the results, it is recommended that water from coconuts, especially from young nuts be used as substrate in nata production. It is also recommended that further studies be conducted for the optimization of Acetobacter aceti xylum's pH range requirement in nata de coco production. lastly, it is recommended that the growth-promoting activity of the coconut water be tested on other microorganisms.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Nata de Coco -- Production